2022
DOI: 10.3390/jof8111180
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Arachnoiditis in Patients with Coccidioidomycosis Meningitis—Analysis of Clinical and Imaging Features

Abstract: Background: Coccidioidomycosis meningitis (CM) is the most aggressive form of coccidioidomycosis, requiring lifelong antifungal treatment and often cerebrospinal fluid (CSF) diversion. Long-standing CM can be associated with spinal complications such as arachnoiditis. However, studies describing the frequency, clinical, and imaging characteristics of arachnoiditis in patients with CM are limited. Methods: We identified 133 patients with CM based on CSF culture, PCR, or serology between January 2010 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition to antifungal therapy, immunosuppression should be reduced or reversed whenever possible. 83 85 Treatment recommendations include fluconazole at doses ranging from 400 mg/d to 1200 mg/d and surgery in some cases. 86 Histoplasma Histoplasma capsulatum is endemic to the Ohio and Mississippi River valleys.…”
Section: Aspergillusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to antifungal therapy, immunosuppression should be reduced or reversed whenever possible. 83 85 Treatment recommendations include fluconazole at doses ranging from 400 mg/d to 1200 mg/d and surgery in some cases. 86 Histoplasma Histoplasma capsulatum is endemic to the Ohio and Mississippi River valleys.…”
Section: Aspergillusmentioning
confidence: 99%
“…MRI typically shows variable abnormalities. A 2022 MRI study showed 53% of infected patients had leptomeningeal enhancement, 53% had arachnoiditis, 23% had syringomyelia, 10% had cord signal abnormalities, and 7% had osteomyelitis 85 . Treatment recommendations include fluconazole at doses ranging from 400 mg/d to 1200 mg/d and surgery in some cases 86 …”
Section: Fungal Myelopathiesmentioning
confidence: 99%